2015
DOI: 10.1007/s11104-015-2650-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant-associated microbiomes in arid lands: diversity, ecology and biotechnological potential

Abstract: 17Background Aridification is a worldwide serious threat directly affecting agriculture and crop production. In arid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 95 publications
(2 reference statements)
3
92
0
Order By: Relevance
“…In arid environments, desert farming favours the selection of drought‐protecting microbial assemblages (Marasco et al ., ; TerHorst et al ., ; Soussi et al ., ) that are enriched and rearranged in the plant rhizosphere and endosphere (Mapelli et al ., ; Marasco et al ., ; ; Cherif et al ., ; Ferjani et al ., ; Santos‐Medellín et al ., ). PGP microorganisms use several mechanisms to stimulate drought tolerance in plants (Vurukonda et al ., ; Etesami and Maheshwari, ): (i) the microbial enzyme 1‐aminocyclopropane‐1‐carboxylate (ACC) deaminase contributes to control the concentration of the plant stress phytohormone ethylene, by degrading its precursor ACC (Glick, ); (ii) microorganisms contribute to modulate plant hormone homeostasis by producing auxin [i.e., indole‐3‐acetic acid (IAA)], cytokinins and giberellins.…”
Section: Introductionmentioning
confidence: 99%
“…In arid environments, desert farming favours the selection of drought‐protecting microbial assemblages (Marasco et al ., ; TerHorst et al ., ; Soussi et al ., ) that are enriched and rearranged in the plant rhizosphere and endosphere (Mapelli et al ., ; Marasco et al ., ; ; Cherif et al ., ; Ferjani et al ., ; Santos‐Medellín et al ., ). PGP microorganisms use several mechanisms to stimulate drought tolerance in plants (Vurukonda et al ., ; Etesami and Maheshwari, ): (i) the microbial enzyme 1‐aminocyclopropane‐1‐carboxylate (ACC) deaminase contributes to control the concentration of the plant stress phytohormone ethylene, by degrading its precursor ACC (Glick, ); (ii) microorganisms contribute to modulate plant hormone homeostasis by producing auxin [i.e., indole‐3‐acetic acid (IAA)], cytokinins and giberellins.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research has reported weaker responses of the bacterial alpha-than beta-diversity to the vegetation loss [5,48]. These substantial changes in the bacterial beta-diversity could be due to the substantial percentage of the abundant (19-35%) and rare (21-30%) phylotypes that responded to the vegetation loss across the N-enrichment levels, although previous studies have reported such changes at the phylum level [49]. The large changes in the fungal beta-diversity could be due to the substantial percentage of rare (35-48%) than abundant fungal phylotypes that responded to vegetation loss across N-enrichment levels.…”
Section: Effects Of Vegetation Loss On Microbial Beta Diversity Acrosmentioning
confidence: 83%
“…Endophytes that reside inside the plant tissues not only take care of its host plant health but also fight against the plant pathogens which can be extended its usage as bioinoculants for field crops. Antagonistic activity exhibited by bacterial endophytes makes them suitable for the use of biocontrol agents and these endophytes colonize actively in the host plant tissues and establish a beneficial lifelong active association with the plant without harming them [1,2,3,4,5,6]. The endophytic microbial community finds its entry into the host tissues from the rhizosphere zone in the soil [7].…”
Section: Introductionmentioning
confidence: 99%